Breaking news or breaking the newspaper? Print journalists, online journalists and their medium-based loyalties - Tandoc, Edson C. Jr (Plaridel, 2014)
Access online through this link: https://www.plarideljournal.org/article/breaking-news-or-breaking-the-newspaper-print-journalists-online-journalists-and-their-medium-based-loyalties